UMP is focused on its strategy to be the best technology university - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) is now moving to the next level to fulfil its objective of becoming the leading technology university, the phase for Creating Glory which starts from 2016 until 2020.